Bionomics of Olibrus bicolor (Fabricius) (Coleoptera Phalacridae) (Bollettino di zoologia agraria e bachicoltura, 2024)
In April-May, larvae of two Olibrus species were found feeding on flowering capitula of Urospermum dalechampii (L.) Schmidt (Compositae) in Bari province (Southern Italy). Pupae form at soil, and adults emerge in June. Four larval instars were recognized in O. bicolor by measuring both head width and body length in several specimens. Further features of larvae and genital anatomy of egg-bearing females are described.
Keywords: Olibrus bicolor; larval instars; morphology; emergence; genital anatomy